Investigation of sinusoidal shaped rotor to reduce torque ripple in axial flux permanent magnet machine. Issue 1 (31st December 2022) - Nazir, Muhadus; Ikram, Junaid; Yousuf, Muhammad; Hussain Bukhari, Syed Sabir; Shah, Madad Ali; Memon, Ali Asghar; Ro, Jong-Suk
Abstract : Cogging torque is one of the main reasons for torque pulsation in AFPM machines that arises due to the force of attraction between stator slots and rotor poles thus adversely affecting the smoothness of output torque. In this paper, a rotor shape for the axial flux internal rotor (AFIR) PM machine is proposed for cogging torque reduction and smoothing the output torque. In this research, the reduction in cogging torque is accomplished in two stages. In the first stage, a sinusoidal magnet shape is proposed to have less cogging torque as compared to a conventional and arced shaped magnet. In the second stage, the magnet overhang technique is used in the optimisation process of the machine to further improve the performance characteristics. The optimisation process comprises a selection of variables, Latin hypercube sampling (LHS), model approximation by kriging method, and Genetic Algorithm (GA) to get optimum values of variables. Output results of proposed and optimised models are also compared to demonstrate that the optimised model has reduced torque ripples and improved average output torque. Models are simulated using 3D finite element analysis (FEA) for comparative analysis.